Effectiveness and interaction of the association of Flumioxazin and Pyroxasulfone in the control of Guinea grass (Panicum maximum) - Presoto, Jéssica Cursino; Netto, Acácio Gonçalves; Andrade, Jeisiane de Fátima; Malardo, Marcelo Rafael; Nicolai, Marcelo; Christoffoleti, Pedro Jacob (Revista de Ciências Agroveterinárias, 2022)
The infestation of difficult-to-control weeds in a crop has direct negative effects on growth and development as they compete for water, light, and nutrients, in addition to hindering the harvest, and in the specific case of sugarcane they can reduce the longevity of the field. Normally, formulated mixture of herbicides, applied in pre-emergence conditions, is used to achieve a greater weed spectrum, longer residual effect, and lower costs. However, a mixture of two molecules can cause diverse effects, such as antagonism, synergism, or additives effects; therefore, it is important to know the interaction involved in each mixture used. In this way, this work has been developed to assess possible interactions of the association of the herbicides flumioxazin and pyroxasulfone applied in pre-emergence conditions, as well as assessing the effectiveness of the mixture control in Guinea grass (Panicum maximum). The study was conducted in greenhouse conditions in 5 L plastic pots, and the treatments consisted of a 4 x 4 factorial design: four flumioxazin doses (0, 50, 100, and 200 g ha-1) and four pyroxasulfone doses (0, 50, 100, and 200 g ha-1). The experimental design was the randomized block, with percentage control and residual dry mass evaluations at 35 days after application (DAA). The interaction data were analyzed using the Colby’s model, and the control effectiveness data were analyzed using the F-test, followed by Tukey test, when significant. The effectiveness of the association between the herbicides flumioxazin and pyroxasulfone on Guinea grass was proven when applied in pre-emergence conditions with averages above 90% of control. The interaction between the herbicides flumioxazin and pyroxasulfone has been considered additive by Colby’s model.